DESIGN CULTURE OF R&D PROJECT SPECIALIST IN THE LIGHT INDUSTRY - Sergeeva, Marina; Samokhin, Ivan; Sunaeva, Svetlana; Gerasimenko, Irina; Goltseva, Оksana; Gordeeva, Tatiana; Belyakova, Tatiana (Revista Inclusiones, 2020)
A fashion designer (FD) is a person who plays a key role in creating new variants of clothing, shoes, hats and other things of this kind (including accessories). The professional patterns proposed by this worker determine the fit, the potential demand and other important characteristics of the product. Previously, the designer was a specialist who combined a number of professional functions: he/she was responsible for the choice of fabric, the style, the cutting and the sewing. However, in the future many tasks were distributed among other employees: designer, cutter and tailor. Therefore, the FD’s functions have significantly decreased. Currently his/her duties include studying fashion trends, formulating fresh ideas and creating sketches. The technologist processes fabrics, modernizes the production process and improves the tailoring technique. The constructor deals with drawings, i.e. is involved in both technical and artistic aspects of the activity. As a rule, these specialists work together in a team, making a common contribution to the creation of new collections. As for the FD, in most cases he/she is engaged in a ready-made sketch developed by the constructor. In other words, the former is obliged to realize the latter’s creative idea, turn it into a tangible and visible object with the lowest material and technical costs. The FD decides which fabric should be used for a particular model, deals with patterns and templates, provides various approaches to the implementation of the original plan. Thus, we are talking about activities of technical nature with an element of creativity, which requires special education and specific professional skills.